ANALISIS NILAI TAMBAH INDUSTRI PENGOLAHAN RAJUNGAN SEBELUM DAN SELAMA COVID-19 (STUDI KASUS UD.SINAR SARINA AFA) - Fikil Fikil; La Onu La Ola; Laode Muhammad Hazairin; Akhmad Mansyur; Desi Sriwulan (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2022)
The purpose of this study was to examine the production process of crab processing and the value added of the crab processing business before and during COVID-19 (case study of UD. Sinar Sarina Afa). This research uses case study method. This research was conducted in March-April 2021 at UD. Sinar Sarina Afa. Primary data was obtained by interviewing the staff at each stage of the production process. Secondary data from documents at UD. Sinar Sarina Afa. The variables measured/observed by the production activities of crab processing include the weighing of the crab, cleaning, steaming, aerating, releasing the shell, sorting the meat, weighing, packaging, and marketing it as well as the costs used to produce the processed crab. The results of the analysis show that before Covid-19, the value added of the economy created by UD.Sinar Sarina Afa in carrying out each production process was Rp1.635.000., and During Covid-19, the amount of added value was Rp1.270.000.